Comparative evaluation of the impact of minimally invasive preparation vs. conventional straight‐line preparation on tooth biomechanics: a finite element analysis. (5th October 2016) - Yuan, Keyong; Niu, Chenguang; Xie, Qian; Jiang, Wenxin; Gao, Li; Huang, Zhengwei; Ma, Rui
Abstract : Minimally invasive endodontics emphasizes preservation of a maximal amount of healthy tooth tissue. However, whether the tooth structure preserved by minimally invasive endodontics can maintain higher fracture resistance is unclear. This study aimed to compare the biomechanics on teeth after minimally invasive (MI) preparation and straight‐line (SL) preparation using finite element analysis. Six finite element analysis models of a mandibular first molar were constructed and divided into two groups (MI and SL). Two loads of 250 N, one vertically stimulating the vertical masticatory force and the other given 45° to the longitudinal axis of the tooth, were applied. Stresses in the teeth were calculated and analyzed. Under both vertical and 45° loads, the greatest stresses were located at the margin of the cavities on the occlusal surfaces. The stress concentration areas of teeth with minimally invasive access cavities were smaller than those of teeth prepared with straight‐line opening in coronal and cervical areas. The stress concentration points in the cervical areas increased with the increase of canal taper in the coronal third. Minimally invasive access preparation reduced the stress distribution in crown and cervical regions. A smaller taper cervical enlargement caused lower stress in the cervical region.